2015
DOI: 10.1002/jbm.a.35596
|View full text |Cite
|
Sign up to set email alerts
|

New guanidine‐containing nanocomposites impeding the growth of Staphylococcus epidermidis 33 and the biofilm formation

Abstract: New water-soluble nanocomposites (AgNCs) based on Ag and copolymers of 2,2-diallyl-1,1,3,3-tetraethylguanidiniumchloride with N-vinylpyrrolidone [poly(AGC-VP)] and vinylacetate [poly(AGC-VA)] have been developed. Antibacterial action of new silver nanocomposites on S. epidermidis 33 (planctonic cells and biofilms) is reported in this study. AgNCs strongly inhibited biofilms formation of S. epidermidis 33. The viability of S. epidermidis 33 cells in biofilms was considerably reduced by new AgNCs. It has been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…It was shown that administration of silver compounds in different materials prevented bacterial bio lm formation [58]. The antibio lm activity of silver nanoparticles is brie y described in a number of studies [59][60][61][62][63][64][65][66][67][68]. It has been shown that inactivation of bacteria in bio lms occurs at silver nanoparticle concentrations 5-20 times higher than those inhibiting completely the planktonic cells and bio lm formation [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that administration of silver compounds in different materials prevented bacterial bio lm formation [58]. The antibio lm activity of silver nanoparticles is brie y described in a number of studies [59][60][61][62][63][64][65][66][67][68]. It has been shown that inactivation of bacteria in bio lms occurs at silver nanoparticle concentrations 5-20 times higher than those inhibiting completely the planktonic cells and bio lm formation [67,68].…”
Section: Discussionmentioning
confidence: 99%